DOAB Directory of open access books - OAPEN (Open Access Publishing in European Networks).; OpenEdition; CNRS (French National Centre for Scientific Research).; CNRS (Centre National de la Recherche Scientifique).; Aix-Marseille Université; DOAB (Directory of Open Access Books) Foundation; MERCED-I (Mindanao Educational Resources for Curricular Enhancement and Development-Initiatives) on OER (Open Educational Resources). (The Hague, Netherlands OAPEN, OpenEdition, CNRS and Aix-Marseille Université, provided by DOAB Foundation, 2020)
Open Access Books is a joint service of OAPEN, OpenEdition, CNRS and Aix-Marseille Université.
University Library (UL)
mixed.
online.
Keywords: Electronic information resources; Internet research; Internet in higher education; Open learning; Open education; Education, Higher; Electronic books -- Open educational resources